Epidemiological Determinants and Trend Analysis of Dengue Fever Disease - Sutriyawan, Agung; Suherdin, Suherdin; Kurniawati, Ratna Dian (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2024)
Bandung City is an endemic area for dengue fever, with 4,424 cases and 14 deaths. This research aims to analyze the epidemiological determinants and see the trend analysis to forecast dengue hemorrhagic fever cases. This research used a case-control design. The case population was those who suffered from dengue hemorrhagic fever, while the control population was those who did not suffer from dengue hemorrhagic fever. A sample of 510 respondents was taken. Sampling using a purposive sampling technique. Epidemiological determinants were analyzed using the chi-square test and logistic regression, while disease trends used exponential smooth analysis. The related results were education (p=0.036), presence of mosquito larvae (p=0.000), container material (p=0.002), water container (p=0.025), mosquito wire (p=0.010), presence of solid waste (p=0.002), mosquito repellent plants (p=0.041), mobility (p=0.004). The most dominant epidemiological determinant was the presence of mosquito larvae (OR=3.2). The incidence trend of dengue fever is increasing over the next 5 years. The research concluded that the epidemiological determinants of dengue fever were education, the presence of mosquito larvae, container materials, water collection objects, mosquito wires, the presence of solid waste, and mosquito repellent plants. The presence of mosquito larvae was the dominant factor. There is an increase in dengue fever cases over the next 5 years. It is recommended to increase the larva-free rate by optimizing Jumantik cadres and conducting epidemiological surveillance.